내장지방영역이 복강경 위암 수술의 난이도를 예측하는데 도움이 되는가? - 신호정 (The Graduate School, Ajou University, 2017)
Purpose: Obesity is associated with morbidity following gastric cancer surgery, but whether obesity influences morbidity after laparoscopic gastrectomy (LG) remains controversial. The present study evaluated whether body mass index (BMI) and visceral fat area (VFA) predict postoperative complications. Materials and Methods: A total of 217 consecutive patients who had undergone LG for gastric cancer between May 2003 and December 2005 were included in the present study. We divided the patients into two groups (‘before learning curve’ and ‘after learning curve’) based on the learning curve effect of the surgeon. Each of these groups was sub-classified according to BMI (<25 kg/m2 and ≥25 kg/m2) and VFA (<100 cm2 and ≥100 cm2). Surgical outcomes, including operative time, quantity of blood loss, and postoperative complications, were compared between BMI and VFA subgroups. Results: The mean operative time, length of hospital stay, and complication rate were significantly higher in the before learning curve group than in the after learning curve group. In the subgroup analysis, complication rate and length of hospital stay did not differ according to BMI or VFA; however, for the before learning curve group, mean operative time and blood loss were significantly higher in the high VFA subgroup than in the low VFA subgroup (P=0.047 and P=0.028, respectively). Conclusions: VFA may be a better predictive marker than BMI for selecting candidates for LG, which may help to get a better surgical outcome for inexperienced surgeons.
학위논문(석사)--아주대학교 일반대학원 :의학과,2017. 2
Keywords: Stomach neoplasms; Laparoscopic; Gastrectomy; Obesity; Intra-abdominal fat